PANDANGAN TEOLOGIS PENDETA DALAM KASUS BUNUH DIRI DI DAERAH RANTETAYO, TANA TORAJA - Rahel Falensa; Rikki Mangitung, Wahyuni Vikawanti Manglili, Leis Pasae, Agustina Lilis Pamilang (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
One of the social disease that is so widespread in society specifically in Indonesia at the present time is the incident of suicide. The rise of suicide cases occurs in all groups regardless of social strata and human age. This research is motivated by the phenomenon of suicide which is so rife, it is no longer a fabrication but an event that really happened. The author is motivated to examine the role and also the theological views of priests regarding suicide in preventing suicides, especially those that occurred in Rantetayo area, Tana Toraja Regency. The method that the writer uses in this study is a qualitative method which comes from literature studies, interview and observation techniques. It is through research conducted that the quality and role of the church is urgently needed through pastors to prevent cases of suicide through mentoring, sermons, coaching, directions visits, and understanding to members of the Congregation regarding God’s Word. The results of this study state that suicide by faith is not justified and is not an act desired by God because it is contrary to the word of God, because God is the outhority over human life and death